2011
DOI: 10.1108/13612021111112322
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the demand for counterfeit goods

Abstract: PurposeThe production, distribution and consumption of counterfeit goods have been increasing at an alarming rate. Current legislation addresses the supply side of the problem, but not the demand side of the problem. The purpose of this paper is to examine, empirically, factors affecting consumer demand for counterfeit goods were analyzed.Design/methodology/approachThe economic theory of consumer demand provided the theoretical framework. Data were collected from students enrolled at a major mid‐western univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 14 publications
5
67
0
8
Order By: Relevance
“…In Asian countries both buyers and non-buyers of counterfeits irrespective of their income levels consider purchasing of counterfeits a normal buying behavior (Ang et al 2001). Similar situation prevails in the West particularly in USA (Norum, Cuno 2011). US consumers believe that consumption of counterfeits does not hurt US economy (Yoo, Lee 2009).…”
Section: Ethical Sensitivitymentioning
confidence: 98%
See 3 more Smart Citations
“…In Asian countries both buyers and non-buyers of counterfeits irrespective of their income levels consider purchasing of counterfeits a normal buying behavior (Ang et al 2001). Similar situation prevails in the West particularly in USA (Norum, Cuno 2011). US consumers believe that consumption of counterfeits does not hurt US economy (Yoo, Lee 2009).…”
Section: Ethical Sensitivitymentioning
confidence: 98%
“…Past studies (e.g. Lee, Workman 2011;Norum, Cuno 2011;Stumpf et al 2011) identified most of these factors as demand drivers of counterfeits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leaders, managers, designers across the globe have recognized the rapid growth of this trend, and then they come to a decision to work with Union international anti-counterfeiting organizations (IACC) and the Institute of ownership international intellectual (IIPI) to protect their designs from being copied (Norum & Cuno, 2011). Matos (2007) indicated that 5% of the global transaction is a transaction of counterfeit products.…”
Section: Introductionmentioning
confidence: 99%